An Environmentally Friendly and Flexible Aqueous Zinc Battery Using an Organic Cathode - Guo, Zhaowei; Ma, Yuanyuan; Dong, Xiaoli; Huang, Jianhang; Wang, Yonggang; Xia, Yongyao (Angewandte Chemie International Edition, 2018)
Rechargeable batteries have been used to power various electric devices and store energy from renewables, but their toxic components (namely, electrode materials, electrolyte, and separator) generally cause serious environment issues when disused. Such toxicity characteristic makes them difficult to power future wearable electronic devices. Now an environmentally friendly and highly safe rechargeable battery, based on a pyrene‐4,5,9,10‐tetraone (PTO) cathode and zinc anode in mild aqueous electrolyte is presented. The PTO‐cathode shows a high specific capacity (336 mAh g−1) for Zn2+ storage with fast kinetics and high reversibility. Thus, the PTO//Zn full cell exhibits a high energy density (186.7 Wh kg−1), supercapacitor‐like power behavior and long‐term lifespan (over 1000 cycles). Moreover, a belt‐shaped PTO//Zn battery with robust mechanical durability and remarkable flexibility is first fabricated to clarify its potential application in wearable electronic devices. Battery‐à‐porter: An environmentally friendly flexible aqueous zinc battery using an organic cathode exhibits superior electrochemical and flexible performances. It was demonstrated to be a promising large‐scale energy storage device and power source for wearable electronic devices.